Trans-generational Immune Priming in Invertebrates: Current Knowledge and Future Prospects - Tetreau, Guillaume; Dhinaut, Julien; Gourbal, Benjamin; Moret, Yannick (Frontiers in Immunology, 2019)
Trans-generational immune priming (TGIP) refers to the transfer of the parental immunological experience to its progeny, which may result in the protection of the latter from repeated encounters with pathogens that may persist across generations. Although extensively studied in vertebrates for over a century, this phenomenon has only been identified twenty years ago in invertebrates. Since then, invertebrate TGIP has been the focus of an increasing interest, with half of studies published during the last few years. TGIP has now been tested in several invertebrate systems using various experimental approaches and measures to study it at both the functional and the evolutionary levels. However, drawing an overall picture of TGIP from available studies still appears a difficult task. Here, we provide a comprehensive review of TGIP in invertebrates with the objective of confronting all the data generated to date to highlight the main features and mechanisms identified in the context of its ecology and evolution. To this purpose, we describe all the articles reporting experimental investigation of TGIP in invertebrates and propose a critical analysis of the experimental procedures performed to study this phenomenon. We then investigate the outcome of TGIP in the offspring and its ecological and evolutionary relevance before reviewing the potential molecular mechanisms identified to date. In the light of this review, we build hypothetical scenarios of the mechanisms through which TGIP might be achieved, and propose guidelines for future investigations.